An Intravital Microscopy Toolbox to Study Mammary Gland Dynamics from Cellular Level to Organ Scale - Messal, Hendrik A. (J Mammary Gland Biol Neoplasia, 2021)
The architecture of the mouse mammary gland is highly dynamic and constantly remodeled during pubertal development and estrous cycle-driven sprouting and regression of alveolar side branches. During each of these developmental stages, turnover is driven by distinct subsets of mammary epithelial cells. Extensive previous research has shed light on the unique morphological and cell biological characteristics of each stage. However, technological shortcomings failed to capture the dynamics and single-cell contributions to mammary remodeling. Here, we developed in vivo imaging strategies to follow the same mammary ducts over time and quantify the dynamics of mammary gland growth and remodeling from single-cell level to organ scale. Using a combination of intravital microscopy and genetic reporter systems we show how proliferative heterogeneity drives ductal morphogenesis during different developmental stages. To visualize pubertal growth at the cellular level, we performed long-term time-lapse imaging of extending terminal end buds through a mammary imaging window. We show that single-cells within the terminal end buds are extremely motile and continuously exchange position whilst the duct is elongating. To visualize short-term remodeling in the adult mammary gland at the single cell level, we performed multi-day intravital imaging in photoconvertible Kikume Green–Red mice and fluorescent ubiquitination-based cell cycle indicator mice. We demonstrate that the contribution of single-cells to estrous-driven remodeling is highly variable between cells in the same micro-environment. To assess the effects of this dynamic proliferative contribution on the long-term stability of tissue architecture, we developed a repeated skin flap method to assess mammary gland morphology by intravital microscopy over extended time spans for up to six months. Interestingly, in contrast to the short-term dynamic remodeling, the long-term morphology of the mammary gland remains remarkably stable. Together, our tool box of imaging strategies allows to identify and map transient and continuing dynamics of single cells to the architecture of the mammary gland. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10911-021-09487-2.